Modification of systemic anti-cancer therapies and weight loss, a population-level real-world evidence study. (December 2020) - Shaw, Clare; Starling, Naureen; Reich, Adam; Wilkes, Emily; White, Rebecca; Shepelev, Julian; Narduzzi, Silvia
Background: Involuntary weight loss may occur during systemic anti-cancer therapy (SACT), causing treatment disruption and poorer prognoses. There remain gaps in clinical awareness as to which patients may benefit from nutritional interventions that aim to prevent unintended weight loss during SACT. We utilised England's population-level cancer registry data, conducting a pan-cancer assessment of patient weight loss during SACT. We aimed to identify cancers with weight loss-associated treatment modifications, potential beneficiaries of nutritional intervention. Methods: This cross-sectional study used England's Cancer Analysis System database, including SACT-treated adults with one tumour and ⩾2 weight recordings between 2014 and 2018. Binary weight loss (threshold: 2.5%) was derived from patients' most negative weight change from first SACT weight recording. The Martin et al. body mass index-adjusted weight loss grading system (BMI-WLG) was assigned. We describe binary weight loss, BMI-WLG and treatment modification status by cancer. Multivariate logistic regression models of weight loss (binary and BMI-WLG) and a composite outcome of patient treatment-modification status by cancer were produced. Results: Our study population contained 200, 536 patients across 18 cancers; 28% experienced binary weight loss during SACT. Weight loss patients were more likely to have multiple types of treatment modifications recorded across all cancers. Regression analyses included 86, 991 patients. Binary weight loss was associated ( p < 0.05) with higher likelihood of treatment modification in; colon [Odds Ratio (OR) = 1.72, 95% confidence interval (CI): 1.42, 2.07]; gynaecologic (excl. ovarian) (OR = 1.48, 95% CI: 1.08, 2.01); stomach (OR = 1.46, 95% CI: 1.04, 2.06); lung (OR = 1.38, 95% CI: 1.21, 1.58); leukaemia (OR = 1.30, 95% CI: 1.09, 1.55); head and neck (OR = 1.30, 95% CI: 1.02, 1.65) and oesophageal (OR = 1.29, 95% CI: 1.01, 1.64) cancers. In lung, colon, and grouped gastro-intestinal cancers, association between BMI-WLG and treatment modification increased by WLG. Discussion: Our study is a wide assessment of weight loss during SACT using England's cancer registry data. Across different cancers we found patients have weight loss-associated treatment modifications during SACT, a precursor to poorer prognoses. Our findings highlight cancers that may benefit from improved nutritional intervention during SACT.